Barrier methods of contraception, spermicides, and sexually transmitted diseases: a review. Issue 6 (December 1994) - d'Oro, L C; Parazzini, F; Naldi, L; La Vecchia, C
Abstract : OBJECTIVE--To understand whether barrier methods of contraception (BMC) and/or spermicides lower the risk of acquiring sexually transmitted disease (STD) and to quantify the protection. DESIGN--Review of published experimental studies, in vitro and in vivo evidence on the issue. SUBJECTS--We reviewed 22 papers that examined the impermeability of BMC in vitro against STD agents or the effect of spermicides, and 60 papers reporting results of epidemiological studies on the risk of STD in users of BMC. RESULTS--There was in vitro evidence that both BMC and spermicides were effective against most sexually transmissible agents. Doubts remain on the effectiveness of BMC and spermicides in normal conditions of use, particularly against human papilloma virus. Natural membrane condoms are not impermeable and pores are seen by electron microscopy. Epidemiological studies show a consistent reduction in the risk for use of condoms against gonococcal (most studies giving relative risk, RR, estimates around 0.4 to 0.6) and HIV infection (RRs between 0.3 and 0.6 in most studies). Spermicides protect women against gonorrhoea and trichomoniasis; their role against other STDs is less clear and there is some indication of an irritative effect on the vaginal mucosa that is likely to be dose-dependent. CONCLUSIONS--A large amount of evidence indicates that BMC reduce the risk of gonorrhoea and HIV transmission, but the results are--at least in quantitative terms--less consistent for other diseases. Implications for individual choices and public health approaches should relate to frequency of exposure and severity of the disease too.